2013
DOI: 10.1186/1471-2164-14-824
|View full text |Cite
|
Sign up to set email alerts
|

The chromatin modification by SUMO-2/3 but not SUMO-1 prevents the epigenetic activation of key immune-related genes during Kaposi’s sarcoma associated herpesvirus reactivation

Abstract: BackgroundSUMOylation, as part of the epigenetic regulation of transcription, has been intensively studied in lower eukaryotes that contain only a single SUMO protein; however, the functions of SUMOylation during mammalian epigenetic transcriptional regulation are largely uncharacterized. Mammals express three major SUMO paralogues: SUMO-1, SUMO-2, and SUMO-3 (normally referred to as SUMO-1 and SUMO-2/3). Herpesviruses, including Kaposi’s sarcoma associated herpesvirus (KSHV), seem to have evolved mechanisms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 54 publications
(75 reference statements)
2
39
0
Order By: Relevance
“…RNA-seq was performed at the Sequencing Core of National Research Program for Genomic Medicine at the National Yang-Ming University using Illumina HiSeq 2000. Sequencing reads were processed as described previously [21]. In this study, the sequence reads that did not map to hg19 were aligned to the KSHV genome.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA-seq was performed at the Sequencing Core of National Research Program for Genomic Medicine at the National Yang-Ming University using Illumina HiSeq 2000. Sequencing reads were processed as described previously [21]. In this study, the sequence reads that did not map to hg19 were aligned to the KSHV genome.…”
Section: Methodsmentioning
confidence: 99%
“…Genome-wide studies have shown that SUMO modification may associate with either positive regulation [19,20] or negative restraint of gene transcription [2022]. By using Kaposi’s sarcoma associated herpesvirus (KSHV) as a model, we recently showed that SUMO-2/3 specific chromatin modification restrains the transactivation of genes in the KSHV genomic euchromatin region [21,23]. This suggests that SUMO-paralog specific chromatin modifications may be involved in the observed variation in the role of SUMO in epigenetic regulation of transcription.…”
Section: Introductionmentioning
confidence: 99%
“…K‐bZIP is SUMOylated at K158, and SUMOylation is essential for its function as a transcriptional repressor . K‐bZIP is a SUMO E3 ligase, catalyzing the SUMOylation of p53, Rb, IRF‐1, IRF‐2, and itself . K‐bZIP also catalyzes the SUMOylation of heterochromatin histone demethylase JMJD2A .…”
Section: Introductionmentioning
confidence: 99%
“…27 K-bZIP is a SUMO E3 ligase, catalyzing the SUMOylation of p53, Rb, IRF-1, IRF-2, and itself. 31,32 K-bZIP also catalyzes the SUMOylation of heterochromatin histone demethylase JMJD2A. 33 During viral reactivation, higher K-bZIP binding on the SUMO2/3-enriched chromatin region is observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation